2019
DOI: 10.1101/604488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption of membrane cholesterol organization impairs the concerted activity of PIEZO1 channel clusters

Abstract: The essential mammalian mechanosensitive channel PIEZO1 organizes in the plasma membrane into nanometric clusters which depend on the integrity of cholesterol domains to rapidly detect applied force and especially inactivate syncronously, the most commonly altered feature of PIEZO1 in pathology. ABSTRACTThe human mechanosensitive ion channel PIEZO1 is gated by membrane tension and regulates essential biological processes such as vascular development and erythrocyte volume homeostasis. Currently, little is know… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Consistent with these observations, studies of overexpressed channels have also shown no inactivation or slow inactivation. 100 It would seem, therefore, that inactivation is a variable property; its extent depending on context and probably also the type of stimulus. It is also unclear whether the rapid pressure pulses and indentation pulses commonly used in experimental studies have physiological correlates—in physiology, it is more likely that the stimuli are relatively slow changes in membrane tension or fluid flow.…”
Section: Challenges and Controversiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these observations, studies of overexpressed channels have also shown no inactivation or slow inactivation. 100 It would seem, therefore, that inactivation is a variable property; its extent depending on context and probably also the type of stimulus. It is also unclear whether the rapid pressure pulses and indentation pulses commonly used in experimental studies have physiological correlates—in physiology, it is more likely that the stimuli are relatively slow changes in membrane tension or fluid flow.…”
Section: Challenges and Controversiesmentioning
confidence: 99%
“…It is also unclear whether the rapid pressure pulses and indentation pulses commonly used in experimental studies have physiological correlates—in physiology, it is more likely that the stimuli are relatively slow changes in membrane tension or fluid flow. How inactivation is controlled or avoided (inactivation of inactivation) in native systems is not yet clear, but one possibility is regulation by local lipid composition 29,100 (Text Box 5). Lipids could conceivably interact with and disable an inactivation gate, creating a pool of available channels that is variable in number and contribution.…”
Section: Challenges and Controversiesmentioning
confidence: 99%
“…In other studies, cholesterol depletion 54 reduces the activity of ENaC (Balut et al, 2005) and TRPC (Bergdahl et al, 2003) channels. 55 In a recent preprint study, lateral organization of cholesterol in the membrane is reported to 56 regulate Piezo1 activity (Ridone et al, 2019). Further indirect links between cholesterol and 57…”
Section: Introduction 26mentioning
confidence: 99%
“…Functional data point to a role for various lipids in mechanical gating of Piezo1. For example, methyl-b-cyclodextrin, a drug commonly used to deplete cholesterol, had a minor influence on Piezo1 clustering (41), reduced mechanically induced Piezo1 currents in response to cell indentation (42), and increased the pressure required to open the channel in cell-attached patch clamping (41). Depletion of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) via activation of TRPV1 inhibits Piezo1 activity (43).…”
Section: Introductionmentioning
confidence: 99%